Cyclopiazonic acid type indole alkaloids from Nicotiana tabacum-derived fungus Aspergillus versicolor and their anti-tobacco mosaic virus activities. (June 2022) - Yang, Guang-Yu; Dai, Jia-Meng; Mi, Qi-Li; Li, Zhen-Jie; Li, Xue-Mei; Zhang, Jian-Duo; Wang, Jin; Li, Yin-Ke; Wang, Wei-Guang; Zhou, Min; Hu, Qiu-Fen
Abstract: Indole alkaloids have attracted widespread attention of chemists and biologists. Therefore, the aim of this study is to screen more bioactivities indole alkaloids from the microorganisms. In this study, five undescribed CPA-type indole alkaloids, aspergillines F–J, and three known CPA-type indole alkaloids, aspergilline A, aspergilline C, and cyclopiamide E, were obtained from the Nicotiana tabacum - derived fungus Aspergillus versicolor . Notably, aspergillines F and G represent the first examples of indole alkaloids with a benzo[ cd ]indol-2(1 H )-one skeleton, and aspergilline J is also the firstly obtained indole alkaloids bearing a N -1-(2-(1 H -imidazole-5-yl)ethyl) moiety. Aspergillines F–J and cyclopiamide E were tested for their anti-TMV activities, and the results revealed that aspergillines G and J exhibited obvious anti-TMV activities with inhibition rates of 41.2 and 56.8% at the concentration of 20  μ M, respectively. These rates are high than that of positive control (with inhibition rate of 32.5%). In addition, the molecular docking studies for the isolated CPA-type indole alkaloids may also reveal that the benzo[ cd ]indol-2(1 H )-one substructure is the fundamental for anti-TMV activity and the oxygen-containing substituent groups at C-19 also increases the inhibitory activity. This study of structure-activity relationship is helpful to find new anti-TMV activity inhibitors. Graphical abstract: Five undescribed CPA-type indole alkaloids were obtained from N. tabacum -derived fungus A. versicolor . Aspergillines G and J exhibited obvious anti-TMV activities. Image 1 Highlights: Five undescribed CPA-type alkaloids were obtained from fungus A. versicolor . Aspergillines F and G represent the examples of benzo[ cd ]indol-2(1 H )-one skeleton. Aspergilline J is the CPA alkaloids bearing a N -1-(2-(1 H -imidazole-5-yl)ethyl) moiety. Aspergillines G and J exhibited obvious anti-TMV activities.